1993
DOI: 10.1007/bf00420934
|View full text |Cite
|
Sign up to set email alerts
|

Topographic pattern of the rearrangement of the dystrophin gene in Japanese Duchenne muscular dystrophy

Abstract: To compare the frequency and distribution of rearrangements in the dystrophin gene in Duchenne muscular dystrophy (DMD) between Japanese DMD patients and those in North America and Europe, Southern blot analyses of the dystrophin gene were carried out in 88 probands classified as DMD. Gene rearrangements were found in 61 (69%) subjects, and they were composed of partial gene deletions in 53 (60%) probands and partial duplications in 7 (8%) probands. A total deletion of the gene was found in 1 (1%) patient. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
1
3
1
Order By: Relevance
“…In the case of Japanese patients, frequency of deletions [43%, Sugino et al, 1989;43%, Tsukamoto et al, 1991] was lower than that observed in the present study and in studies in the US [Baumbach et al, 1989;Darras et al, 1988] and Europe [Hodgson et al, 1989;Gillard et al, 1989;Den Dunnen et al, 1989;Niemann-Seyde et al, 1992;Covone et al, 1992]. However, Imoto et al [1993] reported a higher frequency (60%). Tsukamoto et al [1991] studied only 28 patients and analyzed only nine exons.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…In the case of Japanese patients, frequency of deletions [43%, Sugino et al, 1989;43%, Tsukamoto et al, 1991] was lower than that observed in the present study and in studies in the US [Baumbach et al, 1989;Darras et al, 1988] and Europe [Hodgson et al, 1989;Gillard et al, 1989;Den Dunnen et al, 1989;Niemann-Seyde et al, 1992;Covone et al, 1992]. However, Imoto et al [1993] reported a higher frequency (60%). Tsukamoto et al [1991] studied only 28 patients and analyzed only nine exons.…”
Section: Discussioncontrasting
confidence: 55%
“…From Table III it is clear that, whenever cDNA probes covering the whole gene were used for Southern analysis [Darras et al, 1988;Hodgson et al, 1989;Den Dunnen et al, 1989;Gillard et al, 1989;Baumbach et al, 1989;Imoto et al, 1993], or whenever most of the primers covering the two "hot spot" regions were used for PCR amplifications Niemann-Seyde et al, 1992; present study], the frequency of deletions observed was similar. Interestingly, Covone et al [1992] used 30 primer sets, and the frequency of deletions was almost the same as that in the present study, where 27 primer sets were used for PCR amplification.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The percentage of deletions (72.5%) seen in the present study matches with most Indian studies [13][14][15]17] and the sites of deletions are similar to the available information from studies of various populations [18][19][20][21][22][23][24][25][26].…”
Section: Discussionsupporting
confidence: 90%
“…Table 2 compares the detection rates published from Europe, North America and Asia. The detection rate from North American and European studies varied from 55 to 70% [12, 13, 14], while from Asia it was much lower, being 40–43% in Japan [15], 45–50% in Chinese DMD patients [16] and 55% in Thailand [17]. In all of these studies except one, only multiplex I or II or both or cDNA probes were used.…”
Section: Discussionmentioning
confidence: 99%